2020
DOI: 10.3171/2019.7.spine181164
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of the aging spine: a cross-sectional analysis of spinopelvic parameters in the asymptomatic population

Abstract: OBJECTIVEThere have been numerous studies demonstrating increased pain and disability when patients’ spinopelvic parameters fall outside of certain accepted ranges. However, these values were established based on patients suffering from spinal deformities. It remains unknown how these parameters change over a lifetime in asymptomatic individuals. The goal of this study was to define a range of spinopelvic parameters from asymptomatic individuals. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…In addition, we found significant differences in curvature between younger and older healthy participants. More specifically, consistent with the existing spinal cord literature, cervical vertebrae two to four appear to increase in curvature with age [22][23][24][35][36][37][38].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, we found significant differences in curvature between younger and older healthy participants. More specifically, consistent with the existing spinal cord literature, cervical vertebrae two to four appear to increase in curvature with age [22][23][24][35][36][37][38].…”
Section: Discussionsupporting
confidence: 81%
“…Upon analyzing 21 studies, the authors found curvature was not significantly different between symptomatic and asymptomatic individuals, and age was not significantly associated with amount of lordotic cervical curvature. Interestingly, other studies have found that the angle of cervical lordosis tends to increase with age [34][35][36][37]. The parameter of interest for all of these studies was cervical lordosis -where the spine is curving posteriorly (see the image to the left of Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, within 2 days after PKP, SVA decreased, ll and SSA increased, but after long-term followup, we found that with the increase of patients' age, SVA increased gradually, but there was no significant change in VAS score and ODI score, which indicated that sagittal kyphosis can be a natural trend of human degeneration (13). Nevertheless, with the SVA increases and the body leans forward, the pressure on the anterior column of the spine increases, and then the possibility of secondary vertebral fractures may increases significantly (18).…”
Section: Imaging Results Pre-and Post-operationmentioning
confidence: 51%
“…As a result, PKP could not only stable the fractured vertebra body and reveal the severe pain immediately, but also restore the vertebral body height and correct the local kyphosis by inflating of the balloon (6,9,10). However, there is no study investigate the influence of PKP on the (12)(13)(14). In patients with severe sagittal imbalance of entire spine, posterior rotation of the pelvis around the hip joint takes place to compensate for sagittal imbalance even to a small extent and that this compensatory mechanism leads to a decrease in sacral slope and an increase in pelvic tilt.…”
Section: Imaging Results Pre-and Post-operationmentioning
confidence: 99%
“…6 It is generally recognized that lumbopelvic parameters vary depending on age and gender. [7][8][9][10][11][12] However, there has been no study clarifying detailed age-and gender-specific values of CT-evaluated lumbopelvic parameters. Therefore, this study was designed to understand how spinopelvic alignment in the supine position changes age dependently in each gender.…”
Section: Introductionmentioning
confidence: 99%